Regulacja prawna ochrony danych osobowych we Francji: [Legal regulation of personal data protection in France] (Studia Prawnicze / The Legal Studies, 1982)
Considering real threats accompanying application of computer techniques in the domain of gathering, registration, storage and processing of personal data, the majority of highly industralized states were obliged to pass legal acts of the highest rank in order to regulate position of an individual, whose personal data were used as a basis for the above mantioned processes. One of the most recent statutes which came into being was French law of January 6, 1978 on protection of personal data. Presentation of general principles and provisions, as well as interpretation of this act and its supplementing decrees, was the purpose of this study.The material is divided into six basic parts. Introductory part contains axio- logical considerations relating to application of automatic data processing techni- ques to personal data, and it contains the genesis and reasons for passing legal acts of this very kind.In the second part, purposes, subject matter and scope of statutory protection were discussed. Presented statute invokes several other important problems such as e.g. interest for human rights and citizen’s rights, traditional for French legal system, or more recent issues such as e.g. the right to privacy of life and the right to preserve one’s proper identity.The third part of the study deals with control and supervision over the realization of provisions of this law. Duties in this domain are fulfilled by an organ specially created, i.e. by the National Commission for Automated Data Processing and Rights of Man. This organ’s position is specific as compared with other state bodies, since the legislator empowers it with broad competence in the domain of decision making; it is an advisory organ of the government.The fourth part discusses protection of data in internal relations with parti- cular attention brought to formal requirments necessary to begin processing of data. Also, the issue of protection of data in the process of gethering, registration, storage and processing was brought up, as well as rights of subjects of information, i.e. persons to whome the data to be processed relate.In the fifth part, provisions concerning data processing outside French territory were presented. The last part of this study contains summing up and conclusions.